KONSUMSI DAN INFLASI INDONESIA - Muh.Nur, Ermon; Amar, Syamsul; Syofyan, Efrizal (Program Studi Magister Ilmu Ekonomi, 2012)
AbstractThis study aims to analyze and observes (1) the effect of inflation, disposable income, interest rates and the previous period consumption to inflation in Indonesia. (2) the effect of consumption, interest rate and excange rates and the money supply to Indonesia Inflation. The type of research is descriptive and associative studies. The type of data that used is documentary data, the source of data is secondary data sources. data is in the form of time series from first quarter of 2000 – to fourth quarter of 2010. This study utilize a simultaneous equation model analysis by means of two stages Least Squared method (TSLS). Endogenous variable in this study is the consumption and inflation. While the eksogen variable is the excange rate,money supply,interest rates disposable income, and previous period consumption. The study yields conclusion that (1)inflation,disposable income, interest rates and the previous period consumption have a significant effect on consumtion in Indonesia. In a way that. If there is a decrease of inflation, disposable income and previous consumption have increased the consumption in Indonesia will increase. Conversely, if there is an increasing in consumtion, excange rate (depreciation) and the money supply while the interest rates go down then it will impact an increase in inflation in Indonesia. Vice versa if there is a decrease of consumption, exchange rate (appreciation) and the money supply, while the interest rates rise it will have an impact on reducing Indonesia inflation. Keywords: inflation, consumption, disposable income, interest rates and the consumption of the previous period, exchange rate, and the money supply.